Sports medicine in soccer (Medycyna sportowa, 2000)
Z. Jastrzebski: The assessment of anaerobic capacity of football players G. Lutoslawska, E. Hübner-Wozniak: Overtraining syndrome - symptoms, mechanisms, detection A. Grzybowski, W. Radzioch: Soccer-related injuries - an analysis of records of the Sports Medicine Centre in Czestochowa S. Nowerski: Traumatic injuries of the urogenital system in athletes B. Góralczyki i wsp.: Detection and treatment of Achilles tendon injuries